Affinity of Glycan‐Modified Nanodiamonds towards Lectins and Uropathogenic Escherichia Coli. Issue 4 (24th February 2016) - Turcheniuk, Volodymyr; Turcheniuk, Kostiantyn; Bouckaert, Julie; Barras, Alexandre; Dumych, Tetiana; Bilyy, Rostyslav; Zaitsev, Vladimir; Siriwardena, Aloysius; Wang, Qi; Boukherroub, Rabah; Szunerits, Sabine
Abstract: Nanodiamond particles (NDs) modified with glycan ligands are revealing themselves to have great promise as new nanomaterials for combating biofilm formation and as promising anti‐adhesive scaffolds. Currently, the strategies at hand to formulate glycan‐modified NDs (glyco‐NDs) are limited to a few reports. We demonstrate herein that the photoinduced covalent attachment of unmodified sugars results in glyco‐NDs with high binding affinity to lectins and a uropathogenic Escherichia coli strain ( E. coli UTI89). While the binding affinities of glyco‐NDs to different lectins is partially sacrificed when monosaccharides such as mannose are photochemically integrated onto NDs, in the case of disaccharides and oligosaccharides the binding affinity of glyco‐NDs to lectins is preserved. Moreover, mannan‐modified NDs show strong interactions with uropathogenic E. coli ., suggesting the effectiveness of photochemically formed glyco‐NDs for disruption of E. coli ‐mediated biofilms. Abstract : The photoinduced covalent attachment of unmodified sugars to nanodiamonds (NDs) gives glyco‐NDs with a high binding affinity to lectins and a uropathogenic Escherichia coli strain ( E. coli UTI89). The mannan‐modified NDs show strong interactions with E. coli ., suggesting the effectiveness of photochemically formed glyco‐NDs for disruption of E. coli ‐mediated biofilms.